Perspektif Pembuktian Terhadap Tindak Pidana Cabul Berdasarkan Laporan Polisi (Studi Kasus Di Kepolisian Sektor Concong, Kabupaten Indragiri Hilir) - Asdiansyah; Vivi Arfiani Siregar; KMS. Novyar Satriawan Fikri (Indragiri Law Review, 2026)
This study aims to analyze the perspective of evidence in the crime of indecent acts (cabul) based on a police report at the Concong Sector Police, and to identify the obstacles encountered in the evidentiary process. This research employs an empirical (sociological) legal research method with a descriptive-analytical approach, using primary data obtained through interviews with investigators, the suspect, the victim, and witnesses, supported by secondary data from statutes, legal literature, and prior research. The findings indicate that evidence in cases of indecent acts against minors is built primarily upon witness testimony, including the unsworn statement of the child victim under Article 171 of the Criminal Procedure Code, which is strengthened when consistent with other witness statements, expert testimony in the form of a medical examination report (visum et repertum), and the statement of the suspect, in accordance with the minimum evidentiary standard of Article 183 and Article 184 of the Criminal Procedure Code. However, the evidentiary process faces several obstacles, namely the private and non-witnessed nature of the offence, the psychological vulnerability of the child victim in providing testimony, the time gap between the incident and medical examination, and the reluctance of the community to report such cases. Therefore, strengthening victim-sensitive investigative techniques and multidisciplinary cooperation between investigators, medical personnel, and psychologists is essential to achieve legal certainty and justice for the victim.